Alcohol Use Disorder Moderates the Effect of Age on Heart Rate Variability in Veterans With Posttraumatic Stress Disorder. Issue 10 (October 2017) - Ray, John M.; Pyne, Jeffrey M.; Gevirtz, Richard N.
Abstract : Abstract: Research on heart rate variability (HRV) in posttraumatic stress disorder (PTSD) and comorbid alcohol use disorder (AUD) is limited despite its use as a biomarker of both disorders. This study examined whether AUD comorbidity contributes an additive effect on HRV for veterans with PTSD. HRV was assessed in 70 male Operation Enduring Freedom/Operation Iraqi Freedom veterans with PTSD, including 32 with co-occurring AUD. Mean HRV values for both groups were below the mean for healthy adults, but additive effects of PTSD and AUD on HRV were not observed. Consistent with prior studies, hierarchical regressions showed that HRV decreased with age in the PTSD-only group. However, HRV increased slightly with age among veterans with both PTSD and AUD. This interaction remained significant after controlling for common HRV covariates. These findings support HRV as a biomarker of PTSD and extend research by demonstrating the complex relationship between PTSD and HRV in the context of co-occurring AUD.